2021
DOI: 10.1007/s11104-021-05054-0
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and ecological engineering jointly induced vegetation greening in global karst regions from 2001 to 2020

Abstract: Backgrounds Vegetation dynamic plays a dominant role in the global carbon cycle and climate, especially in vulnerable karst ecosystem. Many studies have examined past several decades changes in vegetation greenness and the associated with climate drivers. Yet, few studies have analyzed the vegetation change in global karst regions particularly in the last decades when climate change and anthropogenic disturbance widely occurred.Methods In this study, we investigated the spatio-temporal variations of vegetation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…About 45% of these forests were planted in SWC, making this region a global hotspot for carbon sinks [27]. Previous studies have established that SWC functions as a significant carbon sink [8,23]. Nonetheless, our study uncovered that one-tenth of the area underwent negative reversals, primarily manifesting after 2010 in the eastern regions of Sichuan, Chongqing, and Guizhou.…”
Section: Nonlinear Trends Of Carbon Sinksmentioning
confidence: 60%
See 2 more Smart Citations
“…About 45% of these forests were planted in SWC, making this region a global hotspot for carbon sinks [27]. Previous studies have established that SWC functions as a significant carbon sink [8,23]. Nonetheless, our study uncovered that one-tenth of the area underwent negative reversals, primarily manifesting after 2010 in the eastern regions of Sichuan, Chongqing, and Guizhou.…”
Section: Nonlinear Trends Of Carbon Sinksmentioning
confidence: 60%
“…Previous studies have estimated the carbon storage in the karst areas through biomass and soil carbon storage surveys, flux tower observations, and remote sensing models. They concluded that the dissolution of carbonate rocks prevents the stable absorption of atmospheric CO 2 , leading to carbon release into the water and turning the region into a carbon source [6,[8][9][10]. Consequently, uncertainty persists in assessing carbon sinks in the karst regions, necessitating further research into estimation methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moderate wind speeds accelerate leaf transpiration rates, enhance plant net photosynthetic rates, and consequently promote vegetation growth (Zhang, Xu, et al, 2022). Generally, the positive impact of human activities improves vegetation coverage, resulting in further ecological improvements (Huang et al, 2022). Conversely, unreasonable human activities can destroy surface vegetation, and population growth, economic development, and urban expansion inevitably lead to vegetation browning (Cao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%